2019
DOI: 10.18689/mjaes-1000102
|View full text |Cite
|
Sign up to set email alerts
|

Innovative Slope Stability and Displacement Analyses

Abstract: Conventional methods of slope stability provides a constant value of safety factor for the slope, providing no information of slope displacements and possible variations of safety margins along the potential failure surface. To overcome this drawback, an innovative approach is proposed here, which takes into account all limit equilibrium requirements originally adopted in the conventional slope stability analyses, with a displacement compatibility function and a hyperbolic shear stress-displacement soil model.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…A case study on a well-monitored slope during a rainstorm showed that the measured slope displacement caused by an elevated groundwater table can be simulated using the proposed method along with hyperbolic soil parameters obtained in large-scale direct shear tests [2].…”
Section: Introductionmentioning
confidence: 99%
“…A case study on a well-monitored slope during a rainstorm showed that the measured slope displacement caused by an elevated groundwater table can be simulated using the proposed method along with hyperbolic soil parameters obtained in large-scale direct shear tests [2].…”
Section: Introductionmentioning
confidence: 99%